ANALISIS KINERJA KEUANGAN DAN STRATEGI KEBERLANJUTAN PADA KOPERASI KUD “X” PEKALONGAN - M. Shofiyuddin; M. Sigit Taruna (Jurnal Ekonomi Dan Bisnis, 2020)
Financial performance in this study was measured and analyzed with the ratio of liquidity, solvency, and profitability. The analysis showed that the performance of KUD “x” showed unhealthy performance. By conducting as a SWOT analysis, the sustainability strategy that can be carried out by the KUD is revitalizing cooperative membership, cooperative asset inventory, rationalizing and evaluating employee needs. Keywords: Low member participation, cooperative debt, unemployed assets, government intervention.